In ovo nano-silver and nutrient supplementation improves immunity and resistance against Newcastle disease virus challenge in broiler chickens - Bhanja, Subrat Kumar; Rath, Pradeepta Kumar; Goel, Akshat; Mehra, Manish; Dhara, Sujoy K.; Paswan, Vinod K.; Attia, Youssef A.; Alqhtani, Abdulmohsen Hussen; Ali, Ahmed B. A.; Shehata, Abdelrazeq M. (Frontiers in Veterinary Science, 2022)
Silver nanoparticles (AgNPs) interact with the microbes and host immune system to protect against diseases. Fertile broiler eggs (n=900) were allotted to six groups: un-injected control, sham (sterile water), AgNPs (50µg), AgNPs+AAs (Methionine-10mg + Arginine-25mg), AgNPs+Vits (Vit B1-72µg + Vit B6-140µg) and AgNPs+TEs (Zn-80µg and Se-0.3µg) and incubated for 18 days. On 18th embryonic day, 0.6 ml test solution was injected at the broad end of egg using 25mm needle and transferred to hatcher. Post-hatch, half of the chicks from each group were vaccinated with Newcastle Disease (ND) vaccine and the other half were kept as un-vaccinated unit and reared for 42 d with standard management practices. Hatchability, 1st and 42nd d body weight, feed intake and feed conversion ratio were similar between treatment groups in both vaccinated and un-vaccinated units. Relative weight of bursa Fabricius and thymus was similar, but spleen weight was higher (P≤0.05) in AgNPs, AgNPs+Vits and AgNPs+TEs chicks than control group. Cellular immune response (against mitogen PHA-P) was higher (P≤0.05) in AgNPs+TEs chicks, whereas HA titer against SRBC antigen, serum IgG, IgM and HI titer against ND vaccine was apparently higher in AgNPs+Vits group chicks than control. No clinical symptoms were observed in the vaccinated groups except for a few control birds six days post challenge (PC). Three days PC, unvaccinated birds show depression, off-feed, greenish diarrhea and nasal discharge and the control group started dying. The highest cumulative infection (CI) was observed in sham (79.17%) and un-injected control (75%), but lowest in AgNPs+AAs birds (58.33%). The CI reached 100% on five dpi in control groups, and 91.67% and 93.75% in AgNPs+TEs and AgNPs+AAs group, respectively. The AgNPs+TEs and AgNPs+AAs group birds lived for more than 90 hrs compared to 75 hrs in control groups and were also had higher IL-6 and IL-2 gene expressions at 24 hrs PC. It was concluded that 50 µg/egg AgNPs with vitamins (B1& B6) and trace elements (Zn & Se) improved performance but AgNPs with trace elements and amino acids enhanced immune response and resistance against vND virus challenge in broilers.